Genome-wide analysis of hepatic DNA methylation reveals impact of epigenetic aging on xenobiotic metabolism and transport genes in an aged mouse model - Sara Abudahab; Mohamad M. Kronfol; Mikhail G. Dozmorov; Thomas Campbell; Fay M. Jahr; Jasmine Nguyen; Ola AlAzzeh; Dalia Y. Al Saeedy; Ashley Victor; Sera Lee; Shravani Malay; Dana M. Lapato; et al. (GeroScience, 2024)
Hepatic xenobiotic metabolism and transport decline with age, while intact xenobiotic metabolism is associated with longevity. However, few studies have examined the genome-wide impact of epigenetic aging on these processes. We used reduced representation bisulfite sequencing (RRBS) to map DNA methylation changes in liver DNA from mice ages 4 and 24 months. We identified several thousand age-associated differentially methylated sites (a-DMS), many of which overlapped genes encoding Phase I and Phase II drug metabolizing enzymes, in addition to ABC and SLC classes of transporters. Notable genes harboring a-DMS were Cyp1a2 , Cyp2d9 , and Abcc2 that encode orthologs of the human drug metabolizing enzymes CYP1A2 and CYP2D6, and the multidrug resistance protein 2 (MRP2) transporter. Cyp2d9 hypermethylation with age was significantly associated with reduced gene expression, while Abcc2 expression was unchanged with age. Cyp1a2 lost methylation with age while, counterintuitively, its expression also reduced with age. We hypothesized that age-related dysregulation of the hepatic transcriptional machinery caused down-regulation of genes despite age-related hypomethylation. Bioinformatic analysis of hypomethylated a-DMS in our sample found them to be highly enriched for hepatic nuclear factor 4 alpha (HNF4α) binding sites. HNF4α promotes Cyp1a2 expression and is downregulated with age, which could explain the reduction in Cyp1a2 expression. Overall, our study supports the broad impact of epigenetic aging on xenobiotic metabolism and transport. Future work should evaluate the interplay between hepatic nuclear receptor function and epigenetic aging. These results may have implications for studies of longevity and healthy aging.